2009
DOI: 10.1007/s00011-009-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells

Abstract: Objective and design Tumor necrosis factor-a (TNF-a) is a proinflammatory cytokine that induces apoptosis in a number of cell systems, including osteoblasts. Simvastatin is a potent 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor known as a stimulator for bone formation via promoting osteoblast differentiation and mineralization. This study was designed to examine the role of simvastatin on TNF-a-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The critically suppressed osterix expression and dramatically elevated apoptotic cell proportion strongly suggested that both differentiation suppression and apoptosis induction contributed to the compromised mineralization ability of cementoblasts. An inhibitory effect on the proliferation of cementoblasts was also observed by MTS assay, although no obvious change in the short exposure period groups was observed, similar to the results obtained on MC3T3-E1 cells (Yang et al 2010). This result may be caused by the time-dependent effect of TNF-α on proliferation, and the short exposure period groups demonstrated effects that were too marginal for detection.…”
Section: Discussionsupporting
confidence: 80%
“…The critically suppressed osterix expression and dramatically elevated apoptotic cell proportion strongly suggested that both differentiation suppression and apoptosis induction contributed to the compromised mineralization ability of cementoblasts. An inhibitory effect on the proliferation of cementoblasts was also observed by MTS assay, although no obvious change in the short exposure period groups was observed, similar to the results obtained on MC3T3-E1 cells (Yang et al 2010). This result may be caused by the time-dependent effect of TNF-α on proliferation, and the short exposure period groups demonstrated effects that were too marginal for detection.…”
Section: Discussionsupporting
confidence: 80%